Differential landscape use by forest owls two years after a mixed‐severity wildfire. Issue 10 (11th October 2021) - Duchac, Leila S.; Lesmeister, Damon B.; Dugger, Katie M.; Davis, Raymond J.
Abstract: Owls are important avian predators in forested systems, but little is known about landscape use by most forest‐adapted owl species in environments impacted by mixed‐severity wildfire. To better understand species‐specific patterns of post‐wildfire landscape use within an owl guild, we used passive acoustic monitoring using autonomous recording units. The technology is effective for multi‐species surveys, especially if some species are rare, nocturnal, or difficult to detect by traditional means. In 2017, we surveyed the interior and adjacent unburned areas of a 10, 700‐ha mixed‐severity wildfire that burned in 2015 in southwest Oregon. We used occupancy modeling to identify patterns of landscape use by five species of forest owls: barred owls ( Strix varia ), great horned owls ( Bubo virginianus ), western screech‐owls ( Megascops kennicottii ), northern pygmy‐owls ( Glaucidium gnoma ), and northern saw‐whet owls ( Aegolius acadicus ). Our results showed a positive relationship between increasing fire severity and probability of use by western screech‐owls and a similar but somewhat weaker relationship for northern pygmy‐owls. Barred owls were rarely detected in severely burned areas and their use decreased with increased fire severity. We observed generally low landscape use for great horned owls, which decreased with increased fire severity and at higher elevations. Thus, four out of the five species appeared to use recently burned forests at different levels, with only northern saw‐whet owls showing near‐complete avoidance of the burned area. These findings increase our understanding of the basic ecology of each species and highlight the varied use of burned areas within this community. These previously undocumented patterns of landscape use in burned landscapes should provide insights to managers and policymakers in the Pacific Northwest as climate shifts, and fires may increase in size, frequency, and severity.